Religion as a Counter-Hegemonic Strategy: A Study of KH. Hasyim Asy’ari from Billings’ Perspective - Muhammad Raqib Assidiqi; Luthfiy A. Gani (Universitas Islam Negeri Sumatera Utara, 2026)
This study aims to analyze the conditions that enabled KH. Hasyim Asy’ari’s religiosity to become a strategy of resistance against colonial domination, rather than merely an expression of religious nationalism or a historical event in the struggle for independence. This study also extends the application of Dwight B. Billings’ “Religion as Opposition” framework to the context of anti-colonial Islam in Indonesia. The results indicate that KH. Hasyim Asy’ari’s success in transforming religion into an instrument of resistance was determined by the fulfillment of three structural prerequisites. First, the position of the kiai as an “Organic Intellectual” who maintained an emotional bond with the santri and peasant classes. Second, the organizational autonomy of the Tebuireng Pesantren and Nahdatul Ulama, achieved through economic self-reliance and the rejection of colonial subsidies, thereby creating a space free from colonial cultural hegemony. Third, the construction of a “Plausibility Structure” through the Jihad Resolution fatwa, which established theology as the basis for the obligation to wage war (fardhu ‘ain). In conclusion, KH. Hasyim Asy’ari’s movement was a manifestation of a well-developed positional warfare strategy, proving that religion can metamorphose into an effective counter-hegemonic ideology when supported by leadership that mobilizes the community, institutional autonomy, and a new plausibility structure.